2022
DOI: 10.3389/fpls.2022.1051340
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and broadly applicable method for transient transformation of plants using vertically aligned carbon nanofiber arrays

Abstract: Transient transformation in plants is a useful process for evaluating gene function. However, there is a scarcity of minimally perturbing methods for gene delivery that can be used on multiple organs, plant species, and non-excised tissues. We pioneered and demonstrated the use of vertically aligned carbon nanofiber (VACNF) arrays to efficiently perform transient transformation of different tissues with DNA constructs in multiple plant species. The VACNFs permeabilize plant tissue transiently to allow molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…), protection or at least delayed degradation of cargoes by nanoparticles, prolonged active lifespan of cargoes within plant cells, and the potential for transient expression of exogenous genes without integration into the plant genome. , Jean et al demonstrated the effectiveness of vertically aligned carbon nanofiber (VACNF) in transforming a 11 kb Gateway plasmid carrying YFP into Arabidopsis leaves, resulting in detectable fluorescent signals. However, further optimization the characteristics of VACNF are required to achieve the successful transformation of even larger plasmids . As nanomaterial-mediated gene delivery systems continue to evolve, there is hope that they will enable the successful transformation of large DNA fragments into plant cells independently from native chromosomes.…”
Section: Challenges Of Plant Large Dna Fragment Transformation and Po...mentioning
confidence: 99%
See 1 more Smart Citation
“…), protection or at least delayed degradation of cargoes by nanoparticles, prolonged active lifespan of cargoes within plant cells, and the potential for transient expression of exogenous genes without integration into the plant genome. , Jean et al demonstrated the effectiveness of vertically aligned carbon nanofiber (VACNF) in transforming a 11 kb Gateway plasmid carrying YFP into Arabidopsis leaves, resulting in detectable fluorescent signals. However, further optimization the characteristics of VACNF are required to achieve the successful transformation of even larger plasmids . As nanomaterial-mediated gene delivery systems continue to evolve, there is hope that they will enable the successful transformation of large DNA fragments into plant cells independently from native chromosomes.…”
Section: Challenges Of Plant Large Dna Fragment Transformation and Po...mentioning
confidence: 99%
“…However, further optimization the characteristics of VACNF are required to achieve the successful transformation of even larger plasmids. 97 As nanomaterial-mediated gene delivery systems continue to evolve, there is hope that they will enable the successful transformation of large DNA fragments into plant cells independently from native chromosomes.…”
Section: Transformation and Possible Solutionsmentioning
confidence: 99%
“…Previously, Morgan et al 7 demonstrated the use of carbon nanofibers affixed to rigid silicon substrate to transiently transform leaves of lettuce, N. benthamiana, and poplar, and both leaves and roots of Arabidopsis. Although transformations were successful on a variety of organs, fibers were more difficult to apply to plant tissues with curved surfaces, such as roots or fruits.…”
Section: Introductionmentioning
confidence: 99%
“…To counteract the hydrophobic nature of SU-8, we apply a thin layer of silicon oxide via atomic layer deposition 15 after fibers are embedded in SU-8. Application of fibers on a rigid substrate for biomolecule/dye delivery utilizes the impact force of tweezer tapping described in Davern et al 6 and the on-plant and on-chip methods described in Morgan et al 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation